(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article is considered the analysis of criminal legislation the Republic of Kazakhstan and countries C.I.S. on concept "terrorism" and about measure, punishment on its stop, by the law "About fight with terrorism". Also rises the question about reason and condition of the spreading the terrorism, and development of the